PERSPEKTIF PEMIKIRAN SYED MUHAMMAD NAQUIB AL-ATTAS TENTANG PENDIDIKAN YANG BERADAB - ., Nuryamin (Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study is to describe the thoughts of Syed Muhammad Naquib al-Attas about civilized education. Syed Muhammad Naquib Al-Attas is one of the world leaders who has great attention to the development of educational thought in the Islamic world. In his view of education he consistently uses the term ta'dib. The word ta'dib is an infinitive vermood (masdar) from the root word